Estudo do material lítico do Crasto de Palheiros - Murça : uma primeira proposta metodológica - 1ª parte - Torres, Isidro M. T. (Portvgalia : Revista de Arqueologia do Departamento de Ciências e Técnicas do Património da FLUP, 2018)
The first results frorn the study of the lithic industry from Castro de Palheiros are presented here. Nucleus, core knappers and fiakes are discussed. Further results concerning retouched tools (points, scrapers) and polished artifacts (axes, milfstones) will be published lateron. New methods for the study of lithic tools from the recent Prehistory are proposed here. These new methods are already used at Palheiros.